Pengaruh Gaya Hedonis dan Harga Terhadap Keputusan Pembelian Pada Produk Apple Pada Masyarakat Medan Tenggara II - Nadila Utami; Adelina Lubis; Laila Tawila; Siti Alhamra Salqaura (Universitas Medan Area, 2022)
The purpose of this study was to determine the effect of hedonic style on purchasing decisions on apple products, to determine the effect of price on purchasing decisions on apple products and to determine the effect of hedonic style and price on purchasing decisions on apple products in the people of Medan Tenggara II. The population in this study were the people of Medan Tenggara II Lingkungan XII as many as 80 people, where the sample was 80 people who bought apple products. The data collection technique used in this study was carried out by distributing questionnaires. The analysis technique used in this research is multiple linear regression, partial test (t test), simultaneous significance test (F test) and the coefficient of determination. The results showed that partially there was a significant influence of hedonic style on purchasing decisions, partially that there was a significant effect of price on purchasing decisions, and simultaneously showed that hedonic style and price had a significant effect on purchasing decisions on Apple products in the Southeast Medan Community II. With an R Square value of 0.707 or 70.7%, which means that the influence of hedonic style and price on purchasing decisions is 70.7%, while the remaining 29.3% are other variables not examined by this study, such as promotion, advertising and other variables.